2005
DOI: 10.1002/cyto.a.20165
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal imbalances in laryngeal and hypopharyngeal cancers detected by comparative genomic hybridization

Abstract: Background: The prognostic divergence of laryngeal and hypopharyngeal carcinomas is well known. Hypopharyngeal tumors are characterized by frequent metastasis formation and local recurrence, which is the source of the unfavorable prognosis of this subtype. The aim of this study was to define chromosomal alterations associated with the aggressive behavior of hypopharyngeal tumors. Methods: Twenty-nine head and neck squamous cell carcinomas (larynx n 5 14 and hypopharynx n 5 15) were analyzed by comparative geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Underlying genetic abnormalities may explain this discordance between the clinical outcome and the TNM status or location. 3,4 DNA aneuploidy, such as numerical or structural chromosomal abnormalities, is found in tonsillar carcinomas. 1 Chromosomal instability (CIN) implies that cancer cells lose or gain chromosomes or chromosomal material during mitosis, 5 representing an increased rate of change in chromosomal structure that is associated with an increase in bulk DNA, such as aneuploidy.…”
mentioning
confidence: 99%
“…Underlying genetic abnormalities may explain this discordance between the clinical outcome and the TNM status or location. 3,4 DNA aneuploidy, such as numerical or structural chromosomal abnormalities, is found in tonsillar carcinomas. 1 Chromosomal instability (CIN) implies that cancer cells lose or gain chromosomes or chromosomal material during mitosis, 5 representing an increased rate of change in chromosomal structure that is associated with an increase in bulk DNA, such as aneuploidy.…”
mentioning
confidence: 99%
“…On the other hand, the remaining 8 of the 23 cases did not show a gain in this region, suggesting that this change may not always occur in ESC. Amplification at 11q13 has been reported previously not only in ESC but also in oral cancer, head and neck cancer, nasopharyngeal cancer, and several other types of cancer [21][22][23][24][25]. For example, Hui et al [21] reported this amplification as a 5.3-Mb amplicon at 11q13.1-13.3 as the most frequently detected gain in 26 nasopharyngeal cancers.…”
Section: Discussionmentioning
confidence: 81%
“…The c-MYC protein is a multifunctional transcription factor involved in the activation of DNA replication; overexpression of this protooncogene may induce chromosome aberrations and an overall dysfunction in the regulation of the cell cycle [13, 14, 20, 21]. …”
Section: Discussionmentioning
confidence: 99%